Designing of an Agroindustrial Information System of Pasuruan Regency by the Use of USDP and UWE - Effendi, Usman; Nurika, Irnia; Effendi, Mas'ud (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
This research is addressed for designing an information system provides agro-industrial information of Pasuruan District. This research is conducted with descriptive method. The designâ€™s steps use inception and elaboration steps of USDP and support of UWE at the elaboration. Models that yielded from the research are use case model, conceptual model, navigation space model, navigation structure model, presentation model, deployment diagram and component diagram. A descriptive type of research was conducted to design an agro industrial information system of Pasuruan Regency. The information covered general aspect of the regency, agricultural crops, processing of agricultural crops and their products, agriculture-based industries, and the relevant supporting industries, available reading materials and references, guest lists visiting the sites, and maps of profile of the districts in the regency. The design was carried out by the use of the UnifiedÂ Software Development Process (USDP) and Unified Modeling Language-based Web Engineering (UWE).The design of agro industrial information system developed was able to present use case model, conceptual model, navigation space model, navigation structure model, presentation model, deployment diagram and component diagram. However, it still needed further works to improve the features, especially to provide more details information such as other available agro industrial infrastructures, financial analysis for agro industries. Keywords: Information System, Agro-Industry, USDP, UWE